2020
DOI: 10.3390/vaccines8010138
|View full text |Cite
|
Sign up to set email alerts
|

From Bivariate to Multivariate Analysis of Cytometric Data: Overview of Computational Methods and Their Application in Vaccination Studies

Abstract: Flow and mass cytometry are used to quantify the expression of multiple extracellular or intracellular molecules on single cells, allowing the phenotypic and functional characterization of complex cell populations. Multiparametric flow cytometry is particularly suitable for deep analysis of immune responses after vaccination, as it allows to measure the frequency, the phenotype, and the functional features of antigen-specific cells. When many parameters are investigated simultaneously, it is not feasible to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 101 publications
0
22
0
Order By: Relevance
“…Currently, computational models have been applied to immunology data, for example, for the analysis of a high-dimensional dataset in vaccination studies [107,108], but these models are limited to particular aspects [109,110]. There is the potential for these models to become more sophisticated and to predict how responses to pathogens and vaccines are affected by pre-disposing factors [111,112].…”
Section: Systems Biology and Integrative Analysismentioning
confidence: 99%
“…Currently, computational models have been applied to immunology data, for example, for the analysis of a high-dimensional dataset in vaccination studies [107,108], but these models are limited to particular aspects [109,110]. There is the potential for these models to become more sophisticated and to predict how responses to pathogens and vaccines are affected by pre-disposing factors [111,112].…”
Section: Systems Biology and Integrative Analysismentioning
confidence: 99%
“…The interest in trajectory inference analysis is therefore growing, also due to the measurement of cellular processes at the single‐cell level (eg cell cycle, cell differentiation and cell activation). Through such measurements and marker expression profiles, advanced tools can model trajectories of cell development and the transition between different cell states 137 . The application Wanderlust is an example used for trajectory tracking of cell development and has a wide use.…”
Section: Single‐cell Technologiesmentioning
confidence: 99%
“…In their review, Lucchesi et al presented an overview of computational tools available for the analysis of data from flow cytometry in vaccination studies [ 15 ]. Flow cytometry, and in particular multiparametric flow cytometry, are adequate for the in-depth analysis of immune responses to vaccination.…”
mentioning
confidence: 99%
“…Flow cytometry, and in particular multiparametric flow cytometry, are adequate for the in-depth analysis of immune responses to vaccination. The authors reviewed the usefulness and applicability of several bioinformatics tools, from data pre-processing to automated data analysis and the interpretation of results [ 15 ]. The authors also reported the increasing number of publications using the automated analysis of multidimensional cytometry data, based on searches on the Web of Science, and identified a rising trend starting in 2008, with a stronger increase in the period 2014–2019 [ 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation